2020
DOI: 10.3390/polym12061307
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Micro-Structured LED Diffusion Plate Using Efficient Micro Injection Molding and Micro-Ground Mold Core

Abstract: In this paper, a new style of micro-structured LED (light-emitting diode) diffusion plate was developed using a highly efficient and precise hybrid processing method combined with micro injection molding and micro-grinding technology to realize mass production and low-cost manufacturing of LED lamps with excellent lighting performance. Firstly, the micro-structured mold core with controllable shape accuracy and surface quality was machined by the precision trued V-tip grinding wheel. Then, the micro-structured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Aer this method, the test found that the lighting brightness and processing speed are signicantly improved. 185 In addition to cutting the microstructures, high-speed wire electric discharge machining, laser interference lithography processing, and electrolyte jet processing are used to process high-quality microstructures. The method of manufacturing micro-riblet surface structures on metal plates using high-speed wire electric discharge machining (WEDM-HS) was designed and proposed by Chu et al The surface modied by this method has the advantages of hydrophobicity, low cost, and rapid prototyping.…”
Section: Precision Machiningmentioning
confidence: 99%
See 1 more Smart Citation
“…Aer this method, the test found that the lighting brightness and processing speed are signicantly improved. 185 In addition to cutting the microstructures, high-speed wire electric discharge machining, laser interference lithography processing, and electrolyte jet processing are used to process high-quality microstructures. The method of manufacturing micro-riblet surface structures on metal plates using high-speed wire electric discharge machining (WEDM-HS) was designed and proposed by Chu et al The surface modied by this method has the advantages of hydrophobicity, low cost, and rapid prototyping.…”
Section: Precision Machiningmentioning
confidence: 99%
“…After this method, the test found that the lighting brightness and processing speed are significantly improved. 185 …”
Section: Fabrication Technologymentioning
confidence: 99%
“…Thus, high‐precision technologies have attracted considerable attention in recent years. [ 1,2 ] For example, micro/nanoprocessing of polymers, which pertains to the manufacturing and application of materials to realize the design of industrial products at the micro‐ or nanoscale, is an emerging industry of the 21st century that is considered to hold almost as much potential as the IT and biotechnology fields. [ 3,4 ] In particular, the scale of processing has shifted from the millimeter level (10 −3 m) to the micrometer (10 −6 m) and nanoscale (10 −9 m) levels.…”
Section: Introductionmentioning
confidence: 99%
“…Different material connections can be mechanical [3], adhesive [4], or molten welding connections [5]. CFRP and the polymer material can be used to produce composite parts using the injection-molding process, which is an excellent approach for producing low-cost and highly repeatable composite parts used in various fields, such as IT, healthcare, and the biomedical sector [6][7][8]. Obviously, the connection strength between the above two materials has an important influence on the service life of the composite parts.…”
Section: Introductionmentioning
confidence: 99%